2018
DOI: 10.1155/2018/3275025
|View full text |Cite
|
Sign up to set email alerts
|

A New Model Based on 25-Hydroxyvitamin D3 for Predicting Active Crohn’s Disease in Chinese Patients

Abstract: Background The association between vitamin D3 and activity of Crohn's disease (CD) is unclear in Chinese patients. In this study, we aimed to evaluate the correlations between serum levels of 25-hydroxyvitamin D3 (25(OH)D3) and disease activity and predict active disease based on vitamin D status. Methods Between January 2014 and December 2017, 346 CD patients from the First Affiliated Hospital of Sun Yat-sen University were recruited and categorized into a group with 25(OH)D3 ≤ 20 ng/ml and a group with 25(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…CD patients show high prevalence of vitamin D deficiency and have significantly lower vitamin D levels than do patients with irritable bowel syndrome (169). Serum vitamin D level is negatively correlated with disease activity in CD patients (170). Patients with a low vitamin D level (<30 ng/ml) are more likely to stop anti-TNF therapy early owing to a loss of response (HR = 3.49, 95% CI: 1.34-9.09) (68).…”
Section: Vitamin Dmentioning
confidence: 99%
“…CD patients show high prevalence of vitamin D deficiency and have significantly lower vitamin D levels than do patients with irritable bowel syndrome (169). Serum vitamin D level is negatively correlated with disease activity in CD patients (170). Patients with a low vitamin D level (<30 ng/ml) are more likely to stop anti-TNF therapy early owing to a loss of response (HR = 3.49, 95% CI: 1.34-9.09) (68).…”
Section: Vitamin Dmentioning
confidence: 99%
“…70 Although VD is thought to be associated with nutritional status in CD patients, there have been few studies on the association between the serum VD level and nutritional status in CD patients. [71][72][73][74] A study by Prieto JMI et al illustrated a similar relationship between low weight and micronutrient deficiency in CD patients who were underweight and deficient in micronutrients. 72 In summary, we found that VD was associated with both nutritional deficits and inflammation, and that nutritional deficit was associated with inflammation, suggesting that VD supplementation may play an anti-inflammatory role, improve nutritional status and thus improve prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…Treatment of monocytes with 1,25(OH)2D was found to inhibit lipopolysaccharide (LPS)‐induced p38 phosphorylation as well as IL‐6 and TNF‐ α production, thus preventing excessive activation of pro‐inflammatory responses 70 . Although VD is thought to be associated with nutritional status in CD patients, there have been few studies on the association between the serum VD level and nutritional status in CD patients 71–74 . A study by Prieto JMI et al illustrated a similar relationship between low weight and micronutrient deficiency in CD patients who were underweight and deficient in micronutrients 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating noncoding RNAs, including microRNAs (miRNAs) and long ncRNAs (lncRNAs), also play a role in IBD, and the analysis of miRNAs might help monitor disease activity and stricture phenotypes[ 32 ]. Other newly emerging biomarkers for disease progression risk and activity include cathelicidin[ 40 ], trefoil factor 3[ 41 ], and 25-hydroxyvitamin D3[ 42 ]. Several extracellular matrix (ECM) components and growth factors are important biomarkers indicating intestinal fibrosis and stenosis[ 32 ].…”
Section: Biomarkersmentioning
confidence: 99%